Research on designers’ behavioral intention toward Artificial Intelligence-Aided Design: integrating the Theory of Planned Behavior and the Technology Acceptance Model - Jiao, Jinchuan; Cao, Xiangnan (Frontiers in Psychology, 2024)
This study explores designers' adoption of AIAD, utilizing the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM). Drawing on extant literature, we proposed a research model and tested it using data from 392 Chinese designers. The results indicate that in terms of AIAD, (a) designers' attitudes towards AIAD (b = 0.259, P < 0.001), subjective norms (b = 0.363, P < 0.001), and perceived behavioral control (b = 0.556, P < 0.001) have significant and positive impacts on their intention to use AIAD; (b) perceived usefulness of AIAD (b = 0.910, P < 0.001) has a positive and significant correlation with attitudes towards AIADwhile perceived ease of use (b = -0.126, P < 0.05) exerts no significant impact on attitudes; (c) the knowledge level of designers (b = -0.149, P < 0.01) has a negative moderating effect on the impact of attitudes towards AIAD on the intention to use them. The present research then discusses its practical significance.